Metabolomics and cytotoxicity of monomethylhydrazine (MMH) and (E)-1, 1, 4, 4-tetramethyl-2-tetrazene (TMTZ), two liquid propellants. (October 2018) - Guyot, Laetitia; Machon, Christelle; Honorat, Myléne; Manship, Brigitte; Bouard, Charlotte; Vigneron, Arnaud; Puisieux, Alain; Labarthe, Emilie; Jacob, Guy; Dhenain, Anne; Guitton, Jérôme; Payen, Léa
Abstract: Hydrazine-based liquid propellants are routinely used for space rocket propulsion, in particular monomethylhydrazine (MMH), although such compounds are highly hazardous. For several years, great efforts were devoted to developing a less hazardous molecule. To explore the toxicological effects of an alternative compound, namely (E)-1, 1, 4, 4-tetramethyl-2-tetrazene (TMTZ), we exposed various cellular animal and human models to this compound and to the reference compound MMH. We observed no cytotoxic effects following exposure to TMTZ in animal, as well as human models. However, although the three animal models were unaffected by MMH, exposure of the human hepatic HepaRG cell model revealed that apoptotic cytotoxic effects were only detectable in proliferative human hepatic HepaRG cells and not in differentiated cells, although major biochemical modifications were uncovered in the latter. The present findings indicate that the metabolic mechanisms of MMH toxicity is close to those described for hydrazine with numerous biochemical alterations induced by mitochondrial disruption, production of radical species, and aminotransferase inhibition. The alternative TMTZ molecule had little impact on cellular viability and proliferation of rodent and human dermic and hepatic cell models. TMTZ did not produce any metabolomic effects and appears to be a promising putative industrial alternative to MMH. Highlights: MMH treatment induce apoptotic death in proliferative human HepaRG cells. The metabolic mechanisms of MMH toxicity are similar to those described for hydrazine. TMTZ does not produce any metabolomics effects in differentiated human HepaRG cells. MMH produces metabolomics effects in differentiated human HepaRG cells.